Dust Exposure to the Lung Function Capacity of Limestone Industry Workers in West Bandung Regency (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
According to the International Labor Organization (ILO) data in 2013, 30% to 50% of workers in developing countries suffer from pneumoconiosis. Besides, the ILO detected that around 40,000 new cases of pneumoconiosis (respiratory disease) caused by workplace dust exposure occur throughout the world each year. The purpose of this study was to determine the relationship of limestone dust exposure to lung function capacity in the limestone processing industry workers. This type of research is an observational descriptive using a cross-sectional approach. The population is 166 workers from 3 limestone companies in the area of the Cipatat Health Center, West Bandung Regency, 150 workers of PT. Batu Wangi, 8 workers from PT. Tunas Putra, and 8 workers from PT. BP. The sampling technique uses stratified sampling. The number of samples was 32 workers. Data analysis to look for relationships between variables using the Chi-Square formula. The results of the study were 56.2% of workers had normal lung function capacity, and 43.8% of workers had abnormal lung function capacity. There are 66.7% of companies having dust exposure levels according to TLV, and 33.3% exceeding TLV. Chi-square Analysis Results, p-value = 1,000 (> 0.05), so that there is no relationship between lime dust exposure and lung function capacity. The conclusion of the study, there is no relationship between limestone dust exposure and lung function capacity in the limestone processing industry workers. Keywords: Dust exposure, limestone, lung capacity